IMPLEMENTASI KETERAMPILAN PERENCANAAN AKADEMIK DALAM KEPEMIMPINAN KEPALA SEKOLAH - Fahmi, Agus (Universitas Pendidikan Mandalika, 2021)
Abstract: The Principal's Leadership function must be placed proportionally according to his capacity. Self improvement from a leader has a broad meaning in the implementation of academic planning which is required to be able to carry out his responsibilities properly and correctly. So that it can improve teacher performance in the teaching and learning process, where the effectiveness of leadership if applied by a leader will be able to create an effective and efficient teaching and learning process. The formulation of the problem in this research is